Prenatal diagnosis and management of fetal Long QT syndrome - Tomek, Viktor; Škovránek, Jan; Gebauer, Roman Antonín (Pediatric cardiology, 2009)
This report describes a fetus presenting with second-degree atrioventricular block, sinus bradycardia, and transient ventricular tachycardia with ventriculoatrial dissociation. Long QT syndrome (LQTS) was suspected due to the association of heart rhythm disturbances and very short transmitral early deceleration time. This impaired relaxation of the left ventricle was explained by the extreme prolongation of the refractory period caused by the prolonged relaxation time. The infant was treated successfully with beta-blockers and implantation of a pacemaker. The prognosis is poor when LQTS presents utero or during the first week of life. To date, only a few case reports of a fetus with LQTS have been published.
Keywords: Adrenergic beta-Antagonists; Cardiac Pacing, Artificial; Male; kardiostimulace umělá; prenatální diagnóza; metipranolol; Pregnancy; těhotenství; syndrom dlouhého QT; Adult; trimekain; dospělí; beta blokátory; mužské pohlaví; Fetal Diseases; Metipranolol; Prenatal Diagnosis; lidé; ženské pohlaví; Humans; Anti-Arrhythmia Agents; Financing, Organized; Long QT Syndrome; nemoci plodu; Trimecaine; Female; financování organizované; antiarytmika